2021
DOI: 10.1155/2021/5597118
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Administration Attenuates Kidney Inflammation in Obese Mice Complicated with Polymicrobial Sepsis

Abstract: Obesity is a well-known public health issue around the world. Sepsis is a lethal clinical syndrome that causes multiorgan failure. Obesity may aggravate inflammation in septic patients. Glutamine (GLN) is a nutrient with immune regulatory and anti-inflammatory properties. Since sepsis is a common contributing factor for acute kidney injury (AKI), this study investigated the effects of GLN administration on sepsis-induced inflammation and AKI in obese mice. A high-fat diet which consists of 60% of calories from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…In addition, we further substantiate glutamine’s protective effects on oxidative stress management as we demonstrate that glutamine decreased mROS release, which are mainly produced at the electron transport chain during the oxidative phosphorylation process ( 49 , 50 ). This finding is in accordance with a previous study of glutamine alleviating kidney lipid peroxides’ production in a polymicrobial sepsis mouse model induced by cecal ligation and puncture ( 51 ). Beyond the reduced mROS production, we provide evidence that glutamine ameliorates maximal mitochondrial respiration and a consequent elevated reserve capacity of TECs upon hypoxia.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we further substantiate glutamine’s protective effects on oxidative stress management as we demonstrate that glutamine decreased mROS release, which are mainly produced at the electron transport chain during the oxidative phosphorylation process ( 49 , 50 ). This finding is in accordance with a previous study of glutamine alleviating kidney lipid peroxides’ production in a polymicrobial sepsis mouse model induced by cecal ligation and puncture ( 51 ). Beyond the reduced mROS production, we provide evidence that glutamine ameliorates maximal mitochondrial respiration and a consequent elevated reserve capacity of TECs upon hypoxia.…”
Section: Discussionsupporting
confidence: 93%
“…This probably explains the enrichment of nitrogen and glutamine/glutamate metabolic pathways observed in this study. Glutamine is considered non-essential amino acid under normal physiological condition; however, immune-regulatory and anti-inflammatory properties of glutamine have been reported during inflammatory conditions such as infection, stress, and injury ( Su et al, 2021 ). It has been demonstrated that glutamine is equally as important as glucose as an oxidative fuel for the maintenance of gut and immune cell function ( Newsholme et al, 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have confirmed the effects of drugs and molecular compounds on AKI. For example, intravenously glutamine administration alleviates inflammation in obese mice with sepsis, thereby improving AKI, and this regimen is recommended for abdominal surgery in obese patients to reduce the risk of infection ( Su et al, 2021 ). In coronary artery bypass surgery, taking aspirin within 24 h before surgery reduced the incidence of AKI after surgery by 36% and was independently associated ( Aboul-Hassan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%